Odpowiedzi

2009-05-26T17:54:39+02:00
(7-3)(3+7)= 7²-3²=49-9=40
(a-3)² - (a+4)(4-a)-6(3-a)²=(a²-6a+9) - (a²-4²) - 6(-a²-6a+9)=a²-6a+9-a²+16+6a²+36a-54=6a²+30a-29
2009-05-26T17:55:09+02:00
(7-3)(3+7)= 21+49-9-21=40
(a-3)² - (a+4)(4-a)-6(3-a)²= a²-6a+9 - 4a-a²+16-4a-6(9-6a+a²)=
=-6a+9-4a+16-4a-54+36a-6a²=22a-29-6a²
  • Użytkownik Zadane
2009-05-26T17:55:13+02:00
(7-3)(3+7)= 49 - 9 = 40
(a-3)² - (a+4)(4-a) - 6(3-a)² = a² - 6a + 9 - 16 + a² - 6(9 - 6a + a²) = 2a² - 6a - 7 - 54 + 36a - 6a² = -4a² + 30a - 61
2009-05-26T17:55:44+02:00
  • Użytkownik Zadane
2009-05-26T17:56:53+02:00
(7-3)(3+7)=21+49-9-21=40

(a-3)²-(a+4)(4-a)-6(3-a)²=a²-6a+9-(4a-a²+16-4a)-6(9-6a+a²)=
a²-6a+9-4a+a²-16+4a-54+36-6a²=-4a²-6a-25